2003
DOI: 10.1039/b300922j
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical reactions of 2-bromotropone and 2,7-dibromotropone with 9,10-dicyanoanthracene

Abstract: The photochemical reactions of 2-bromotropone and 2,7-dibromotropone with 9,10-dicyanoanthracene gave products with anthracene, anthracenone, and dihydroanthracene skeletons both in polar and non-polar solvents. These products were formed by attack of water contaminated in the solvent, by attack of the troponoid, and by attack of the solvent used in the reactions, respectively, on a reaction intermediate. In a mixed solvent of benzene and methanol, a benzaldehyde derivative with a tribenzo-2-oxabicyclo[3.2.2]n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Similarly, irradiation of a dichloromethane solution of 2,5-dichlorotropone (9) and DCA gave product 10 in 36% yield. The 1 H NMR spectrum indicated that two structures 10a and 10b are possible since the four tropone ring protons appeared as two sets of the AB quartet.…”
Section: Irradiation Of 25-dichlorotroponementioning
confidence: 97%
See 4 more Smart Citations
“…Similarly, irradiation of a dichloromethane solution of 2,5-dichlorotropone (9) and DCA gave product 10 in 36% yield. The 1 H NMR spectrum indicated that two structures 10a and 10b are possible since the four tropone ring protons appeared as two sets of the AB quartet.…”
Section: Irradiation Of 25-dichlorotroponementioning
confidence: 97%
“…An isomer of 13 has been obtained as one of the photoproducts in the reaction of 2,7-dibromotropone and DCA. 9 The chemical shifts Similarly, 2-bromo-5-isopropyltropone (14) gave a bromo derivative 15 of 12 in 85 and 84% yields in benzene and in dichloromethane, respectively and in 69% yield in a mixed solvent of acetonitrile and dichloromethane (Scheme 5).…”
Section: Irradiation Of 2-halo-5-isopropyltroponesmentioning
confidence: 99%
See 3 more Smart Citations